THE IRON METABOLISM IN CHILDREN IS NORMAL ALSO AT INFECTIOUS DISEASES - A. M. Aliyeva; L. S. Namazova-Baranova; Т. V. Kazyukova; V. M. Studenikin (LLC "Diagnostics and Vaccines", 2017)
The authors consistently consider various aspects of iron metabolism in children and in pediatric patients with accompanying infectious process. Special attention is attributed to the problem of combined infections with anemia/iron-deficiency states, non-infectious factors of iron deficiency and anemia in childhood,  as well as to novel approaches to diagnostics of iron metabolism disorders (including the studies of markers such as hepcidin, ferroportin, soluble transferrin receptor, hypoxia inducible factor, divalent metals transporter, etc). Foreign investigations incorporating novel iron metabolism markers in pediatric patients of various ages with infectious/inflammatory disorders are concisely described. The ambiguity and disputability of iron metabolism in pediatric patients against the background of infections and conditions, accompanied with inflammation are stressed.